Populists in government? Hungary's "system of national cooperation". Issue 2 (23rd February 2016) - Batory, Agnes
Abstract : This article considers Hungary's political system from 2010 to 2014 with Fidesz in power and domestic and international actors' responses to the challenge of populists-in-government. The article argues that domestic responses were weakened by Fidesz' use of its supermajority for a partisan redrafting of the country's constitutional order, but also by its mainstream competitors' failure to offer a contrasting yet positive vision for the electorate. External actors, and the European Union (EU) in particular, may therefore have emerged as the main bulwark against the effects of populists-in-government. However, the EU was relatively ill-equipped to deal with systemic violations of the common values of the Union with respect to its member states, and arguably even the available measures were not used to their full potential. The main explanation for this lies in Fidesz' origins: rather than starting its life on the fringes of the electoral space, the party had been the major, mainstream centre-right alternative. This position in Hungary's party system had in turn endowed Fidesz with strong transnational links which outlasted the party's own transformation and continued to act to dampen EU action.